Membrane redox as an essential component of how cells increase in size following cell division - Morré, D. James; Morré, Dorothy M. (Acta Biologica Szegediensis, 2006)
Under investigation is the hypothesis that cell enlargement in both plants and animals is not a passive process but the result of an ECTO-NOX-driven physical membrane displacement. Cell enlargement correlates with ECTO-NOX activity and is stimulated when ECTO-NOX activities are stimulated and inhibited when ECTO-NOX activities are inhibited. Both are blocked by thiol reagents. Additionally, cell enlargement emerges as having an energy requirement. An energy requirement is universal among membrane displacement models and is met at the cell surface through coupling with a plasma membrane-associated AAA-ATPase.